2017
DOI: 10.1016/j.compositesa.2016.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prepreg format on defect control in out-of-autoclave processing

Abstract: Prepreg format plays a key role in part quality for composites produced using vacuum bag only (VBO) techniques. To date, however, VBO prepregs have been produced by modifying existing autoclave formats. In this work, we introduce USCpreg, a prepreg format designed specifically for out-of-autoclave cure, featuring through-thickness permeability. We describe the fabrication and analysis of laminates processed with USCpreg, as well as laminates fabricated from traditional VBO prepreg formats. The through-thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 15 publications
1
27
0
1
Order By: Relevance
“…More complex OoA/VBO composite structures were also evaluated in previous studies. For example, Grunenfelder et al studied the void content in embedded doublers that consisted of a local build‐up of additional plies in regions of laminates and hat‐stiffeners. Results showed that voids within the embedded plies could be reduced by fostering air evacuation through prepreg plies impregnated on only one side and longer vacuum hold times before cure.…”
Section: Introductionmentioning
confidence: 99%
“…More complex OoA/VBO composite structures were also evaluated in previous studies. For example, Grunenfelder et al studied the void content in embedded doublers that consisted of a local build‐up of additional plies in regions of laminates and hat‐stiffeners. Results showed that voids within the embedded plies could be reduced by fostering air evacuation through prepreg plies impregnated on only one side and longer vacuum hold times before cure.…”
Section: Introductionmentioning
confidence: 99%
“…However, for most laminates comprised of UD prepregs, heated debulk is not an effective means to achieve air evacuation prior to cure. To increase transverse air evacuation efficiency in UD prepregs, prepreg formats with discontinuous resin distributions can be a more effective approach [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Anisotropic patterns such as stripes must be intelligently applied to ensure proper placement with reference to the fiber orientation. However, stripes may be simpler and more convenient to produce relative to other pattern designs, such as islands or grid, depending on the production method of the discontinuous resin distribution [6,7,10].…”
Section: Design Considerations and Limitations For Semi-preg Fabricationmentioning
confidence: 99%
“…Previous work has shown that use of OoA/VBO prepregs with a discontinuous resin pattern (semi-pregs) virtually eliminates porosity caused by entrapped air or moisture, without an autoclave cure [6]. For example, Grunenfelder [7][8][9] showed that even under adverse process conditions, parts cured using semi-preg contained near-zero internal porosity and no surface defects. In contrast, conventional VBO prepreg (with continuous resin films) yielded unacceptable levels of porosity (3-8%).…”
Section: Introductionmentioning
confidence: 99%